1991
DOI: 10.1007/bf00118859
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of freezer storage in fulfilling the chilling requirement of fall-lifted ponderosa pine seedlings

Abstract: Application.To ensure that freezer storage will satisfy chilling requirements in fall-lifted ponderosa pine, seedlings should be harvested late in the fall. Lifting seedlings too early in the fall may result in poor shoot development after planting and may delay budbreak even into the second year.Abstract. The degree to which freezer storage fulfilled the chilling requirement of ponderosa pine (Pinus ponderosa Dougl. ex Laws.) seedlings of two sources was determined by monitoring their development after pottin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Although the information is based on only a few genotypes, the pine genotypes evaluated had similar observed responses. However, due to differences in the responses among pine species at low chilling and reported differences in responses to chilling or lack of chilling previously reported for ponderosa pine (Burr et al, 1989 ; Omi et al, 1991 ; Sloan, 1991 ; Wenny et al, 2002 ) we plan to follow up with trials involving more genotypes per pine species. Douglas-fir (Gould et al, 2011 ) and Pacific madrone (this study) both exhibited substantial differences in the possibility lines for genotypes within each species, indicating substantial genetic variation may exist in chilling and forcing requirements for budburst.…”
Section: Discussionmentioning
confidence: 99%
“…Although the information is based on only a few genotypes, the pine genotypes evaluated had similar observed responses. However, due to differences in the responses among pine species at low chilling and reported differences in responses to chilling or lack of chilling previously reported for ponderosa pine (Burr et al, 1989 ; Omi et al, 1991 ; Sloan, 1991 ; Wenny et al, 2002 ) we plan to follow up with trials involving more genotypes per pine species. Douglas-fir (Gould et al, 2011 ) and Pacific madrone (this study) both exhibited substantial differences in the possibility lines for genotypes within each species, indicating substantial genetic variation may exist in chilling and forcing requirements for budburst.…”
Section: Discussionmentioning
confidence: 99%
“…Another commonly used upper-temperature threshold for chilling is 5 °C 11 , 18 . Some studies, however, have suggested that subfreezing temperatures were effective 36 , 37 , so we also tested chilling models using −10 °C as the lower limit. Many studies have also assumed that freezing temperatures did not contribute to winter CA and only included temperatures >0 °C for calculating CA 11 , 38 .…”
Section: Methodsmentioning
confidence: 99%